Poverty trends during two recessions and two recoveries: lessons from Sweden 1991–2013 - Jonsson, J; Mood, C; Bihagen, E (SpringerOpen, 2016)
We study cross-sectional and long-term poverty in Sweden over a period spanning two recessions, and discuss changes in the policy context. We find large increases in absolute poverty and deprivation during the 1990’s recession but much smaller increases in 2008-2010. While increases in non-employment contributed to increasing poverty in the 1990’s, the temporary poverty increase 2008-2010 was entirely due to growing poverty among non-employed. Relative poverty has increased with little variation across business cycles. Outflow from poverty and long-term poverty respond quickly to macro-economic recovery, but around one percent of the working-aged are quite resistant to such improvements.